A Atheneu sergipense: uma casa de educação literária examinada segundo os planos de estudos (1870-1908) - Alves, Eva Maria Siqueira (2005)
Atheneu Sergipense, a public instituition created on October the 24th in 1870 with two courses a School of Humanities and a Normal School had the purpose of offering the youth the secondary instruction necessary to the admission in higher courses, as well as to the execution of many functions in society, and of capacitating professional elementary school teachers. During a certain period of time, the two courses coexisted simultaneously, but this mixed and fragmented function of one only institution was not profitable. Knowing this scenery, the history of Atheneu Sergipense during this period comprehended between the last three decades of the nineteenth century and the first of the twentieth century, investigating this formative space of figures who projected themselves on the social and political landscape, was the aim of this research. At first, my attention was concentrated in works produced in that period and about that period which could recreate the ambient of the city of Aracaju, revealing images of the foundation of Atheneu Sergipense. Focusing on this House of Literary Education, I decided to examine it according to its Plans of Studies (curriculum), making clear their purposes and detaching the elements to be analyzed: chairs (disciplines), time demarcation, textbooks, methodological orientations and systems of evaluation. The analyses were based on a varied repertoire of sources: legislation, reports of directors and governors of Sergipe, minutes of the congregation, sent and received mail, official corrspondence, journalistic texts, chronicles, topics of contest and examination, programs. This investigation could historicize the process of organization of the identity of the instituition, revealing it as a catalyzer of cultural production, of new pedagogical practices, an agglutinative and disseminative center of the cultural ethos , imposing itself as a fair motive of pride to the people of Sergipe